Does the Number of Stimuli Influence the Formation of the Endogenous Components of the Event-Related Auditory Evoked Potentials? - Oliveira, Yorran Marques de; Calderaro, Victor Goiris; Massuda, Eduardo Tanaka; Zanchetta, Sthella; Simões, Humberto de Oliveira (International Archives of Otorhinolaryngology, 2023)
Introduction The number of stimuli is important to determine the quality of auditory evoked potential records. However, there is no consensus on that number in studies, especially in the sample studied.Objectives To investigate the influence of the number of rare stimuli on forming N2 and P3 components, with different types of acoustic stimuli.Methods Cross-sectional, descriptive, comparative study, approved by the ethics committee of the institution. The sample comprised 20 normal hearing adults of both sexes, aged 18 to 29 years old, with normal scores in the mental state examination and auditory processing skills. The event-related auditory evoked potentials were performed with nonverbal (1 kHz versus 2 kHz) and verbal stimuli (/BA/ versus /DA/). The number of rare stimuli varied randomly in the recordings, with 10, 20, 30, 40, and 50 presentations.Results P3 latency was significantly higher for nonverbal stimuli with 50 rare stimuli. N2 latency did not show any difference between the type and number of stimuli. The absolute P3 and N2-P3 amplitudes showed significant differences for both types of stimuli, with higher amplitude for 10 rare stimuli, in contrast with the other ones. The linear tendency test indicated significance only for the amplitude – as the number of rare stimuli increased, the amplitude tended to decrease.Conclusion The components were identifiable in the different numbers of rare stimuli and types of stimuli. The P3 and N2-P3 latency and amplitude increased with fewer verbal and nonverbal stimuli. Recording protocols must consider the number of rare stimuli.
Keywords: evoked potentials; P300 component; hearing; electrophysiology; auditory cortex; healthy volunteers